2016
DOI: 10.1158/0008-5472.can-15-3464
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Omentin as a Novel Biomarker for Colorectal Cancer Risk: Data from the EPIC–Potsdam Cohort Study

Abstract: Omentin is a novel biomarker shown to exert metabolic, inflammatory, and immune-related properties and thereby could be implicated in the risk of colorectal cancer. So far, the association between omentin and colorectal cancer risk has not been evaluated in prospective cohort studies. We investigated the association between prediagnostic plasma omentin concentrations and risk of colorectal cancer in a case-cohort comprising 251 incident colorectal cancer cases diagnosed over a mean follow-up time of 10.4 years… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 40 publications
(46 reference statements)
2
36
1
1
Order By: Relevance
“… 42 Several proinflammatory molecules secreted in adipose tissue and implicated in immune and metabolic pathways have also been associated with CRC, including adiponectin (particularly its non–high-molecular-weight form), soluble leptin receptor, and omentin. 43 , 44 , 45 Our results showing a positive association between chemerin concentration and CRC support those lines of research implicating involvement of immune-inflammatory pathways in colorectal carcinogenesis. While the exact mechanisms explaining the biological association are unclear, several pathways could have a role and be consistent with systemically elevated chemerin concentrations.…”
Section: Discussionsupporting
confidence: 88%
“… 42 Several proinflammatory molecules secreted in adipose tissue and implicated in immune and metabolic pathways have also been associated with CRC, including adiponectin (particularly its non–high-molecular-weight form), soluble leptin receptor, and omentin. 43 , 44 , 45 Our results showing a positive association between chemerin concentration and CRC support those lines of research implicating involvement of immune-inflammatory pathways in colorectal carcinogenesis. While the exact mechanisms explaining the biological association are unclear, several pathways could have a role and be consistent with systemically elevated chemerin concentrations.…”
Section: Discussionsupporting
confidence: 88%
“…Both colorectal and pancreatic cancers are related with obesity, metabolic syndrome and BMI. Recently clinical studies show that cancers such as liver [10], prostate [12] and colorectal [11], [13], [16] are associated with increases in omentin serum levels independent of various factors such as BMI, glucose, lipid parameters, disease differentiation [16]. In a new study, higher omentin concentrations were associated with a higher colorectal cancer risk independent of obesity [16].…”
Section: Discussionmentioning
confidence: 96%
“…These findings indicate that intelectin-1 functions as a tumor suppressor in gastrointestinal cancers. In contrast, Aleksandrova et al reported that a higher intelectin-1 concentration was associated with a higher colorectal cancer risk in a prospective cohort study [72]. These controversial findings may reflect the “ Janus -faced” pathobiological properties of intelectin-1 in various types of carcinogenesis.…”
Section: Intelectin-1 In Colorectal Carcinogenesismentioning
confidence: 99%